In vitro Modeling of Angelman Syndrome using the Neural Commitment of Patient-Specific iPSCs - Vieira, Adriana Andrade (2022)
Tese de mestrado, Biologia Molecular e Genética, Universidade de Lisboa, Faculdade de Ciências, 2020